An Overview of the Coding Standard MPEG-4 Audio Amendments 1 and 2: HE-AAC, SSC, and HE-AAC v2. (3rd June 2009) - den Brinker, A. C.; Breebaart, J.; Ekstrand, P.; Engdegård, J.; Henn, F.; Kjörling, K.; Oomen, W.; Purnhagen, H.
Abstract : In 2003 and 2004, the ISO/IEC MPEG standardization committee added two amendments to their MPEG-4 audio coding standard. These amendments concern parametric coding techniques and encompass Spectral Band Replication (SBR), Sinusoidal Coding (SSC), and Parametric Stereo (PS). In this paper, we will give an overview of the basic ideas behind these techniques and references to more detailed information. Furthermore, the results of listening tests as performed during the final stages of the MPEG-4 standardization process are presented in order to illustrate the performance of these techniques.